Boosting performance and stability of inverted perovskite solar cells by modulating the cathode interface with phenyl phosphine-inlaid semiconducting polymer. (November 2021) - Wang, Gaopeng; Zhang, Kai; Wang, Zheng; Wang, Jian; Xu, Rongguo; Li, Lin; Xu, Xiuwen; Li, Yu; Xiao, Shuang; Zheng, Shizhao; Li, Xiong; Yang, Shihe
Abstract: Cathode interface modulation can improve the charge carrier management and inhibit the unwanted ion/molecular diffusion at the electrode/electron transport layer (ETL) interface, thus play a key role in the long-term operation of high-performance perovskite photovoltaics, but few studies have been focused on understanding the relationship among the molecular structure of cathode interlayer (CIL), the interfacial electronic properties as well as the passivation quality, and the ion/molecular diffusion within the cells. Herein, we report a semi-conducting phenyl phosphine inlaid polymer as a novel CIL between top Ag metal electrode and PCBM, which is essentially an interlayer, in an inverted perovskite solar cell. Even with a perovskite layer prepared in air, the phosphine-inlaid polymer improved power conversation efficiency (PCE) from 16.4% to 20.2%, with the device maintaining 85% of the original efficiency at T = 85 °C after 917 h operation and 80% after 1100 h. Light soaking stability testing showed that the device with PPDIBPP, 85% of the original efficiency could be retained after 560 h. We have proved that the main reason for the device stability enhancement was closely related to the introduction of phosphine in the interlayer, which, besides improving the interfacial energy level alignment and reducing the trap density, could anchor strongly to the Ag electrode as an effective diffusion barrier to Ag and I ions. To our knowledge, such a phenyl-phosphine based polymer is the first to be applied in perovskite solar cells with a simultaneous boost in device efficiency and thermal/lighting stability. Graphical Abstract: ga1 Highlights: A judiciously designed phosphine-inlaid polymer that can coordinate with Ag electrode and interact with iodide. The multi-functional polymer can reduce trap density and prevent ion diffusion. PCEs up to 20.2% even with ambient fabrication, along with a T 80 lifetime > 1100 h under 85 °C aging conditions.